2006
DOI: 10.1111/j.1600-079x.2006.00409.x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Melatonin prevents oxidative stress and changes in antioxidant enzyme expression and activity in the liver of aging rats

Abstract: This study compared the effects of melatonin supplementation on markers of oxidative stress, and on the activity and expression of antioxidant enzymes in the liver of young (3-month-old) and aging (24-month-old) rats. Animals were supplemented with melatonin in the drinking water (20 mg/L) for 4 wk. Liver concentration of thiobarbituric-reactive substances (TBARS), as an index of lipid peroxidation, and the oxidized to reduced glutathione ratio significantly increased in aged rats (+58%), while values did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 70 publications
4
55
0
5
Order By: Relevance
“…Mel and its metabolites have been found to protect tissues against oxidative damage generated by a variety of toxic agents and metabolic processes [41,43,44]. For example, it was found that Mel protects against adriamycin-induced nephrotoxicity [45], Al toxicity in the brain [46,47] and oxidative stress in the liver of ageing rats [48].…”
mentioning
confidence: 99%
“…Mel and its metabolites have been found to protect tissues against oxidative damage generated by a variety of toxic agents and metabolic processes [41,43,44]. For example, it was found that Mel protects against adriamycin-induced nephrotoxicity [45], Al toxicity in the brain [46,47] and oxidative stress in the liver of ageing rats [48].…”
mentioning
confidence: 99%
“…Controversial results have been found in animals exposed to high Cu doses and other oxidative toxics. Decreased SOD activity was appreciated in the liver and/or serum of Cu loaded rats (Roy et al, 2009) that could be due to an increase in protein degradation (Kwon et al, 1998) or nuclear damage caused by Cu toxicity that could affect gene expression, and thus, a decrease of SOD activity (Mauriz et al, 2007;Yu et al, 2008). Thus, according to these authors, the non-increased SOD activity in the Cu-supplemented animals in this study could be explained by the increased protein damage that could lead to a higher SOD degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Bharti et al (28) specified that cerebral epiphyseal proteins and melatonin activated and regulated hepatic and renal antioxidant mechanisms and increased GPx and SOD activity in the liver. In their study, Mauriz et al (29) indicated that melatonin added to potable water (20 mg/L) eliminated oxidative stress in the livers of elderly rats and contributed to the regulation of catalase and CuZn-SOD and GPx gene expressions.…”
Section: Discussionmentioning
confidence: 99%